Anxiety and depression in childhood rheumatologic conditions: A topical review - Mallet R Reid; Jacqueline Fabricius; Ashley Danguecan; Kaveh Ardalan; Andrea Knight; Natoshia R Cunningham (Indian Journal of Rheumatology)
This topical review summarizes recent literature on mental health symptoms experienced by children diagnosed with rheumatologic conditions including childhood-onset systemic lupus erythematosus (cSLE), juvenile idiopathic arthritis (JIA), and juvenile dermatomyositis (JDM). Studies, while limited, generally indicate that anxiety and depressive symptoms may be more common among children diagnosed with rheumatologic conditions than non-chronically ill children. Although the rates of clinically significant symptoms are not consistently reported across studies, overall anxiety and depressive symptom rates in cSLE vary between 34%–37% and 6.7%–59%, respectively. A recent systematic review of JIA suggests between 7% and 64% of participants experienced elevated anxiety, and between 7% and 36% of participants reported clinically significant depressive symptoms. Approximately 40% of youth with JDM may experience general psychological distress, but more research is needed. In the available literature, there is mixed support for higher rates of anxiety in JIA as compared to cSLE, and higher rates of depressive symptoms in cSLE as compared to JIA, whereas mental health functioning in JDM is less well understood. Mental health functioning in youth with rheumatologic conditions may be related to increased disease-related impairment. Using consistent mental health screening measures with clinically validated cutoffs would enhance insight into the frequency and impact of anxiety and depressive symptoms experienced. Knowledge would also be enhanced by conducting studies with ethnically representative samples to identify potential disparities in care. An improved understanding of mental health functioning in pediatric patients presenting for rheumatologic care may inform the development and testing of tailored and effective treatments.